MODELING OF OZONE DUE TO WEATHER CONDITIONS - Souza, Amaury de; Pavão, Hamilton Germano; Pires, José C.M.; Garcia, Ana Paula (Revista Brasileira de Climatologia, 2013)
Ozone concentrations are valuable indicators of possible health and environmental impacts. However, they are also used to monitor changes and trends in the sources of both ozone and its precursors. For this purpose, the influence of meteorological variables is a confusing factor. This study presents an analysis of 4 year of ozone concentrations measured in a Campo Grande-MS-Brazil city. Firstly, the aim of this study was to perceive the daily, monthly and seasonal variation patterns of ozone concentrations. Diurnal cycles are presented by season and the fit of the data to a normal distribution is tested. In order to assess ozone behaviour under weather conditions, local meteorological variables (wind direction and speed, temperature, relative humidity and rainfall) were monitored together with ozone concentrations. The main relationships we could observe in these analyses were then used to obtain a regression equation linking diurnal ozone concentrations with meteorological parameters. The developed model is capable of explaining over 70% of the variability in the ozone concentrations